2017
DOI: 10.1111/josh.12491
|View full text |Cite|
|
Sign up to set email alerts
|

Ten‐Year Secular Trends in Youth Violence: Results From the Philadelphia Youth Risk Behavior Survey 2003‐2013

Abstract: BACKGROUND Youth violence reduction is a public health priority, yet few studies have examined secular trends in violence among urban youth, who may be particularly vulnerable to numerous forms of violence. This study examines 10-year secular trends in the prevalence of violence-related behaviors among Philadelphia high school students. METHODS Repeated cross-sectional data were analyzed from 5 waves of the Philadelphia Youth Risk Behavior Survey (YRBS) from 2003 to 2013. Sex-specific multivariate regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
0
9
0
8
Order By: Relevance
“…During these 6 years, school bullying was unchanged among female students (26.4–26.4%) but decreased significantly among male students (24.5–18.4%) (Schneider et al, ). Previous research with YRBS data from the city of Philadelphia has recommended the examination of trends in youth violence, including bullying victimization by gender (Pool, Patterson, Luna, Hohl, & Bauer, ). Since previous research has shown divergent trends in school bullying victimization by gender, further investigation is needed to examine these trends.…”
Section: Introductionmentioning
confidence: 99%
“…During these 6 years, school bullying was unchanged among female students (26.4–26.4%) but decreased significantly among male students (24.5–18.4%) (Schneider et al, ). Previous research with YRBS data from the city of Philadelphia has recommended the examination of trends in youth violence, including bullying victimization by gender (Pool, Patterson, Luna, Hohl, & Bauer, ). Since previous research has shown divergent trends in school bullying victimization by gender, further investigation is needed to examine these trends.…”
Section: Introductionmentioning
confidence: 99%
“…A variável escolaridade materna apresentou cerca de 18%, 17% e 23% de dados faltantes Idade (anos) ≤ 13 24,4 (23,3-25,5) 19,0 (18,1-19,9) 20,3 (19,3-21,4) 14 47,2 (46,3) 50,1 (49,0-51,2) 52,4 (51,3-53,6) 15 18,2 (17,2-19,3) 19,4 (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)2) 18,5 (17,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)4) ≥16 10,2 (09,4-10,9) 11,5 (10,(6)(7)(8)(9)(10)(11)(12)4) 8,8 (8,…”
Section: Análises De Dadosunclassified
“…Ensino fundamental incompleto 36,1 (34,5) 33,1 (31,9) 27,1 (25,6) Ensino fundamental completo 14,6 (14,1-15,1) 15,7 (15,(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)3) 13,8 (13,(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)5) Ensino médio completo 31,1 (30,2) 34,9 (33,9) 34,8 (33,8) Ensino superior completo 18,2 (17,0-19,4) 16,3 (14,(5)(6)(7)…”
Section: Escolaridade Maternaunclassified
See 2 more Smart Citations